The functions of long non-coding RNAs in neural stem cell proliferation and differentiation - Yanfang Zhao; Hongliang Liu; Qili Zhang; Yuan Zhang (Cell & Bioscience, 2020)
Abstract The capacities for neural stem cells (NSCs) self-renewal with differentiation are need to be precisely regulated for ensuring brain development and homeostasis. Recently, increasing number of studies have highlighted that long non-coding RNAs (lncRNAs) are associated with NSC fate determination during brain development stages. LncRNAs are a class of non-coding RNAs more than 200 nucleotides without protein-coding potential and function as novel critical regulators in multiple biological processes. However, the correlation between lncRNAs and NSC fate decision still need to be explored in-depth. In this review, we will summarize the roles and molecular mechanisms of lncRNAs focusing on NSCs self-renewal, neurogenesis and gliogenesis over the course of neural development, still more, dysregulation of lncRNAs in all stage of neural development have closely relationship with development disorders or glioma. In brief, lncRNAs may be explored as effective modulators in NSCs related neural development and novel biomarkers for diagnosis and prognosis of neurological disorders in the future.